Decent Work Inclusive Policy for Persons with Disabilities in Indonesia - Siti Widharetno Mursalim; Fajrin Nurul Haq (Program Pascasarjana Universitas Negeri Makassar, 2022)
The many problems experienced by persons with disabilities such as difficulty in getting a job, discrimination, and inequality when getting a suitable job and fairness during work indicate that the same service for all citizens has not been fully felt. This is also due to the fact that policy studies that are inclusive of persons with disabilities have not yet been fully implemented. This study uses qualitative research methods and then describes the results of the research descriptively. The final result of this research is a strategy to provide equality for persons with disabilities in employment services.